A Meta-Analysis of Placebo-Controlled Trials of Psychedelic-Assisted Therapy. Issue 4 (7th August 2020) - Luoma, Jason B.; Chwyl, Christina; Bathje, Geoff J.; Davis, Alan K.; Lancelotta, Rafael
ABSTRACT: After a two-decade hiatus in which research on psychedelics was essentially halted, placebo-controlled clinical trials of psychedelic-assisted therapy for mental health conditions have begun to be published. We identified nine randomized, placebo-controlled clinical trials of psychedelic-assisted therapy published since 1994. Studies examined psilocybin, LSD (lysergic acid diethylamide), ayahuasca (which contains a combination of N, N-dimethyltryptamine and harmala monoamine oxidase inhibitor alkaloids), and MDMA (3, 4-methylenedioxymethamphetamine). We compared the standardized mean difference between the experimental and placebo control group at the primary endpoint. Results indicated a significant mean between-groups effect size of 1.21 (Hedges g ), which is larger than the typical effect size found in trials of psychopharmacological or psychotherapy interventions. For the three studies that maintained a placebo control through a follow-up assessment, effects were generally maintained at follow-up. Overall, analyses support the efficacy of psychedelic-assisted therapy across four mental health conditions – post-traumatic stress disorder, anxiety/depression associated with a life-threatening illness, unipolar depression, and social anxiety among autistic adults. While study quality was high, we identify several areas for improvement regarding the conduct and reporting of trials. Larger trials with more diverse samples are needed to examine possible moderators and mediators of effects, and to establish whether effects are maintained over time.